Implementasi Etika Bisnis dan Kepemimpinan Islam (Studi Kasus Pada Toko Muhammad Alfatih 1453) - Andrianto, Imam (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2024)
This study aims to determine how business ethics and Islamic leadership are implemented at Toko Muhammad Alfatih 1453. The study employs a qualitative method, gathering data through interviews and observations. Analysis is conducted on the business practices and leadership of the store, considering the principles of Islamic business ethics and leadership. Questions addressed include the implementation of Islamic business ethics principles in daily business transactions, the application of Islamic leadership principles in managing the team and the store, and the impact of these practices on business performance and customer perception. Based on the research findings, the store has implemented various principles and values of Islamic business ethics, including honesty, financial management based on Sharia principles, social responsibility and sustainability, ethics in customer relations, and Islamic activities and regulations. Additionally, the store also applies Islamic leadership principles, such as mobilizing followers, developing followers, and organizing followers.